Parasites (Isopoda: Epicaridea and Nematoda) from ghost and mud shrimp (Decapoda: Axiidea and Gebiidea) with descriptions of a new genus and a new species of bopyrid isopod and clarification of Pseudione Kossmann, 1881 - Boyko, Christopher B.; Williams, Jason D.; Shields, Jeffrey D. (Zootaxa, 2017)
Ghost and mud shrimps in Axiidea and Gebiidea are hosts to parasitic epicaridean isopods, including species in Bopyridae and Ionidae. These isopods can reach high prevalence levels on their mud shrimp hosts and may strongly influence host ecology and biology. Currently, 54 species of bopyrids and eight species of ionids are known to parasitize ghost and mud shrimps. We present new taxonomic data on three species of ionids and ten species of bopyrids (nine previously described and one new to science), as well as on an undescribed species of nematode from an axiidean host. New locality and host records are given for all species. Our analysis of new material and review of museum specimens includes the description of the new species Acrobelione halimedae n. sp. from Austinogebia spinfrons (Haswell, 1881). We also provide an improved definition for the genus Pseudione Kossmann, 1881, based on morphological characters found in both sexes, and resolution of the type species, P. callianassae Kossmann, 1881. In our revision of Pseudione we erect a new genus, Robinione, and placed two species therein: R. overstreeti (Adkison & Heard, 1995) and R. brattstroemi (Stuardo, Vega & Cespedes, 1986). In addition, two other species are removed from Pseudione: P. compressa (Shiino, 1964) is moved to Ionella Bonnier, 1900, and P. panopei Pearse, 1947 is considered a synonym of Progebiophilus upogebiae (Hay, 1917). Bopyrid isopods represent a large, diverse taxon and our findings help clarify the taxonomy of those species found on ghost and mud shrimps.